Perancangan Sistem Informasi Pengendalian Persediaan Bahan Bangunan - Vivi Arisandhy; David Try Liputra; Jonathan Chandra; Viter Pranata; Tonny Cahyadi (Universitas Katolik Parahyangan, 2023)
Inventory management is important for companies so that optimal efficiency and effectiveness can be achieved. With modern information technology and data management, companies can use inventory information systems to manage data in a more structured and efficient way. Many studies related to inventory information systems have been carried out. However, in those studies, the designed information systems have not been able to issue automatic warnings for inventories that are about to run out. The object of this research is TB X. Previous research has designed an inventory information system at TB X which still requires the user to operate it manually, namely in terms of transferring operational software data to a spreadsheet for methods calculation and vice versa. Therefore, in this research an information system will be designed so that the company can control its inventory more easily. The design of the inventory control information system uses the waterfall method and the application test uses the black box testing method. The design of the inventory control information system will implement the Q method algorithm. Based on the research results, it is known that the designed information system has advantages over previous research, namely being able to issue warning statuses automatically, easier to control inventory compared to the manual method, faster in finding the information needed, more environmentally friendly because it is paperless , making procedures more orderly and avoiding repetitive data errors or missing data, more accurate profit calculations because the system is directly calculated according to sales transaction data, and more accurate or reducing errors in recording the amount of inventory stored compared to the manual method.